The rites controversies in the early modern world - Županov, Ines G. (Studies in Christian Mission, 2018)
The Rites Controversies in the Early Modern World is a collection of fourteen articles focusing on debates concerning the nature of "rites" raging in intellectual circles of Europe, Asia and America in the seventeenth and eighteenth centuries. The controversy started in Jesuit Asian missions where the method of accommodation, based on translation of Christianity into Asian cultural idioms, created a distinction between civic and religious customs. Civic customs were defined as those that could be included into Christianity and permitted to the new converts. However, there was no universal consensus among the various actors in these controversies as to how to establish criteria for distinguishing civility from religion. The controversy had not been resolved, but opened the way to radical religious scepticism. Contributors are: Claudia Brosseder, Michela Catto, Gita Dharampal-Frick, Pierre Antoine Fabre, Ana Carolina Hosne, Ronnie Po-Chia Hsia, Giuseppe Marcocci, Ovidiu Olar, Sabina Pavone, István Perczel, Nicholas Standaert, Margherita Trento, Guillermo Wilde and Ines G. Županov.